2018
DOI: 10.1111/nyas.13673
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic heterogeneity of obesity‐related brain vulnerability: one‐size interventions will not fit all

Abstract: Intact memory and problem solving are key to functional independence and quality of life in older age. Considering the unprecedented demographic shift toward a greater number of older adults than children in the United States in the next few decades, it is critically important for older adults to maintain work productivity and functional independence for as long as possible. Implementing early interventions focused on modifiable risk factors for cognitive decline at midlife is a strategy with the highest chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 160 publications
(276 reference statements)
1
12
0
Order By: Relevance
“…Though there is some tendency for VRFs to co-occur, our simultaneous modelling indicated that smoking, hypertension, pulse pressure, diabetes, and WHR each made unique statistical contributions to lower global brain and higher WMH volumes. Whereas it is possible that associations between obesity and brain structure are partly attributable to the findings that obesity promotes arterial stiffness, it is possible that the unique statistical contributions identified herein could pertain to other mechanisms through which body composition is linked to negative brain and cognitive endpoints, including metabolic and endocrine routes, which may have independent neurovascular consequences 17 , 26 , 48 . Similarly, the unique contributions to brain structure made by hypertension and smoking may indicate that the deleterious effects of smoking on the brain extend beyond putative alterations in hypertension 49 .…”
Section: Discussionmentioning
confidence: 95%
“…Though there is some tendency for VRFs to co-occur, our simultaneous modelling indicated that smoking, hypertension, pulse pressure, diabetes, and WHR each made unique statistical contributions to lower global brain and higher WMH volumes. Whereas it is possible that associations between obesity and brain structure are partly attributable to the findings that obesity promotes arterial stiffness, it is possible that the unique statistical contributions identified herein could pertain to other mechanisms through which body composition is linked to negative brain and cognitive endpoints, including metabolic and endocrine routes, which may have independent neurovascular consequences 17 , 26 , 48 . Similarly, the unique contributions to brain structure made by hypertension and smoking may indicate that the deleterious effects of smoking on the brain extend beyond putative alterations in hypertension 49 .…”
Section: Discussionmentioning
confidence: 95%
“…Though there is some tendency for VRFs to co-occur, our simultaneous modelling indicated that smoking, hypertension, pulse pressure, diabetes and WHR each made unique statistical contributions to lower global brain and higher WMH volumes. Whereas it is possible that associations between obesity and brain structure are partly attributable to the findings that obesity promotes arterial stiffness, it is possible that the unique statistical contributions identified herein could pertain to other mechanisms through which body composition is linked to negative brain and cognitive endpoints, including metabolic and endocrine routes, which may have independent neurovascular consequences 17,24,45 . Similarly, the unique contributions to brain structure made by hypertension and smoking may indicate that the deleterious effects of smoking on the brain extend beyond putative alterations in hypertension 46 .…”
Section: Discussionmentioning
confidence: 95%
“…Cerebral small vessel disease (CSVD; a constellation of clinical and imaging findings of presumed vascular aetiology 13 ) causes ~45% of dementia and 20% of stroke worldwide 14 , though its pathophysiology and the interplay among its many possible determinants are not well understood 13 . Though the specific mechanisms by which these determinants, often known as vascular risk factors (VRFs), remain to be fully elucidated, anthropometric indices (waist:hip ratio and body mass index; WHR and BMI), blood glucose, elevated pulse pressure, chronic hypertension, diabetes and hypercholesterolaemia are all putative VRFs that have been associated with cerebrovascular complications [15][16][17][18] . The resultant damage to cerebral vasculature and increased vascular resistance are thought to deregulate cerebral blood flow, alongside blood brain barrier dysfunction, and could further lead to abnormal protein synthesis and formation of Alzheimer's disease-typical plaques and tangles 15,18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…One of the discussed studies was able to show that smoking had unique statistical contributions to brain morphology when modelling against many other vascular risk factors (VRFs) in a large population (N=9,722) (Cox et al ., 2019); these findings indicate that there some brain areas may be more susceptible to smoking. As VRFs (such as smoking) associate with various adverse outcomes including cognitive ageing and dementia (Haley et al ., 2018; Pasha et al ., 2018; Sweeney et al ., 2018; Cheng et al ., 2020), areas such as BA46 may be more susceptible to ageing and effects that underpin cognitive function, as they show the strongest VRF-related coupling in blood and brain. A larger sample with more detailed regional sampling across the brain will be required to investigate this.…”
Section: Discussionmentioning
confidence: 99%